Could trapping tiny ions crack the toughest codes?. - Minkel, J.R (IEEE spectrum)
Computers that harness the weirdness of quantum mechanics could smash conventional encryption systems by factoring gigantic numbers fast-and factoring the product of two large prime numbers is the only way standard codes can be broken. The job would take conventional computers decades, not minutes. Encrypted data is still safe for the moment, because a powerful enough quantum computer is still many years away. But physicists have now demonstrated that quantum calculations can be done in a version of a quantum computer that could, in theory at least, be scaled up sufficiently. Rainer Blatt and his colleagues at the University of Innsbruck (Austria), in collaboration with Isaac Chuang of the Massachusetts Institute of Technology (MIT), have run a simple quantum algorithm in a computer that consists of only a single, very cold calcium ion. They employed a standard ion-trapping technique and a series of carefully tuned laser pulses to turn the ion into a computer that calculates using qubits-bits that can exist, seemingly paradoxically, as both a 1 and a 0 simultaneously. The Innsbruck-M IT team put this property of qubits to work in the Deutsch-Jozsa algorithm.